What makes Russian women (un)happy? A closer look at the family - Ekaterina Selezneva (Osteuropa-Institut Regensburg, 2010)
Two decades of economic transition revealed that Russian women are on average less happy than men. This paper addresses individual subjective well-being from the intra-family perspective and investigates whether the gender satisfaction gap could be caused, among all, by a mismatch between the socially imposed patriarchal family gender roles and the actually performed ones. I test for the presence of the following phenomena: (1) a fair share of income brought by each of the spouses into their household is judged according to the patriarchal model attributing the role of the breadwinner to men; (2) division of housework, with women, even if working, holding the main responsibility for housekeeping activities, is perceived as fair. Prime-age working adults living in partnership constitute the dataset which is a part of the Russian Longitudinal Monitoring Survey for 1994-2004. Life satisfaction is modelled with the help of the seemingly unrelated bivariate ordered probit model aiming at the adjustment for unobserved factors influencing happiness evaluation of both partners. For the period 1994-1998, the results show that women's relative unhappiness is likely to be causes by their increasing earning powers with relative to men, and overload with hours spent on housekeeping in households with children. In the second period of economic growth, 2000 - 2004, I observe a change in women's preferences over time-use and total income shares, suggesting a tendency towards their emancipation.
Keywords: 330; Frauen; Zufriedenheit; Weibliche Arbeitskräfte; Hausarbeit; Geschlechterdiskriminierung; Gleichberechtigung; Schätzung; Russland